Enantioselective Synthesis of (+)-Agelasidine A Using Thio-Claisen Rearrangement - Ichikawa, Yoshiyasu; Ochi, Rika; Masuda, Toshiya (Synthesis, 2022)
Enantioselective synthesis of the marine natural product (+)-agelasidine A has been achieved by taking advantage of [1,3]-chirality transfer from enantiomerically enriched α-silyl farnesol through a key thio-Claisen rearrangement. The optical rotation of the hydrochloride salt of the synthetic substance confirmed that natural (+)-agelasidine A has the S-configuration at its C-10 stereogenic center.
Keywords: agelasidine A; marine natural product; chirality transfer; thio-Claisen rearrangement